2020
DOI: 10.3390/su12187252
|View full text |Cite
|
Sign up to set email alerts
|

Determinant Factors Influencing Thai Tourists’ Intentions to Use Social Media for Travel Planning

Abstract: Currently, information technology plays an important role in the tourism industry. Tourists like to use social media more widely for their travel planning, which affects the high competition between entrepreneurs while facing the challenge of improving the quality of data services provided through social media. This study developed a model of the relationships between structure factors that affect intentions to use social media for travel planning. The said model integrates the technology acceptance model (TAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 95 publications
8
38
0
3
Order By: Relevance
“…Meanwhile, in order to establish the relationships proposed in the model, partial least square structural equation modeling (PLS-SEM) was employed. The WarpPLS 7.0 [10,154] was utilized to analyze the model structure of this study. According to Kock [155], WarpPLS is "a partial least square regression procedure that is effective for analyzing both linear and non-linear relationship simultaneously" [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, in order to establish the relationships proposed in the model, partial least square structural equation modeling (PLS-SEM) was employed. The WarpPLS 7.0 [10,154] was utilized to analyze the model structure of this study. According to Kock [155], WarpPLS is "a partial least square regression procedure that is effective for analyzing both linear and non-linear relationship simultaneously" [10].…”
Section: Discussionmentioning
confidence: 99%
“…Revisiting a tourist's destination can only be achieved through satisfied tourists who may recommend the destinations to others. Therefore, dissatisfied tourists may express negative comments about a destination and damage the destination's market reputation [10,129]. Baker and Crompton [36] suggested that festival managers should focus their evaluative resources on assessing both festival quality and satisfaction level of attendees.…”
Section: Electronic Word Of Mouth (Ewom) As a Determinantmentioning
confidence: 99%
See 1 more Smart Citation
“…They are an ideal tool for finding information to plan travel and allow the tourist to make decisions in a simple and easy way. The bottom line is that the traveler shares a post related to an interesting tourist attraction, a route, as well as his experience in this journey, through social media, which attracts the attention and interest of other members of social networks (Cheunkamon et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…At present, information technology (Cheunkamon et al 2020;Cai et al 2019;Natorina 2020) plays an important role in a globalized world. Firoiu and Croitoru (2015) focus on the impact of information technology on the development of enterprises providing services to the international tourism industry.…”
Section: Literature Reviewmentioning
confidence: 99%